Para-Sulphonato-calix[n]arene capped silver nanoparticles challenge the catalytic efficiency and the stability of a novel human gut serine protease inhibitor. Issue 61 (9th July 2019) - Akermi, Nizar; Mkaouar, Hela; Kriaa, Aicha; Jablaoui, Amin; Soussou, Souha; Gargouri, Ali; Coleman, Anthony W.; Perret, Florent; Maguin, Emmanuelle; Rhimi, Moez
Abstract : Eubacterium saburreum serpin from human gut microbiota inhibits the pancreatic elastase associated with pancreatitis, inhibition is strongly increased by para -sulphonato-calix[8]arene silver nanoparticles. Abstract : The Eubacterium saburreum serine protease inhibitor from the human gut microbiota inhibits the eukaryotic pancreatic elastase associated with acute pancreatitis. Interestingly, the inhibition efficiency and stability are markedly increased by the para -sulphonato-calix[8]arene capped silver nanoparticles. Moreover, this enzyme is distinguishable by its high inhibitory effect at broad pH range between 2–10 and temperatures from 10 to 40 °C, in the presence of para -sulphonato-calix[8]arene capped silver nanoparticles the enzyme remains active even at 70 °C.